The influence of the auditor’s going concern opinion on investors’ decision - Arunsopha, Phraiporn (2020)
The audit report is considered as an essential qualitative data for stakeholders, especially for an issue regarding a going concern. Therefore, the research aims to examine the information content of an unqualified opinion with an explanatory paragraph regarding a going concern (GCO). The study seeks to identify the impact of the GCO on stock returns and explore whether the impact of the GCO exists after the audit opinion changes back to an unqualified opinion (UNQO). The value relevance model is employed using U.S. company data collected over 4 years from 2015-2018. This model relates stock returns to a change in earnings and incorporates dummy variables regarding audit opinion types and other control variables. Regression is estimated by a fixed-effect model. The results show that compared to the continuing UNQO, stock returns are significantly lower in case that the audit opinion changes from the UNQO to the GCO (i.e., the first-time GCO) but are basically the same in case that the audit opinion changes from the GCO back to the UNQO. This means that the issuance of the GCO adversely affects stock returns; however, this effect does not continue if the company subsequently receives the UNQO. Overall, the results support the information theory and the lending credibility theory. The auditor’s going concern opinion is perceived to be credible and informative by investors, thereby affecting their investment decision. These findings highlight the importance of the going concern assessment by auditors towards investors’ decision and underline the necessity of well-established auditing framework.